Identification of a human Ia antigen that is different from HLA-DR and DC antigens. - Makgoba, M; Hildreth, J; Mcmichael, A (Springer-Verlag, 1983)
A monoclonal antibody, MHM4, identified a cell surface antigen present on B cells and not resting T cells. It precipitated two polypeptide chains of 34 000 and 28 000 daltons from B lymphoblastoid cells. This antibody bound to all B-cell lines tested, except those homozygous for HLA-DR7. Saturation binding assays and Scatchard plots of MHM4 binding to cells that did not carry HLA-DR7 indicated that this antibody bound less than the total surface Ia antigen. When the antibody was competed with eight other HLA-D-specific antibodies, the epitope recognized was shown to be distinct. Two-dimensional gel analysis revealed that a simple pattern of spots was precipitated, unlike the complex patterns obtained with other HLA-D-specific antibodies. The alpha and beta spots were different from those precipitated by HLA-DR- or DC-specific antibodies. It is argued that the MHM4 antigen is the product of an HLA locus that is distinct from HLA-DR and DC. Its relationship with HLA-SB is discussed.